Simulating the construction management process - M. Rojas, Eddy; Mukherjee, Amlan (Revista Ingeniería de Construcción, 2006)
This paper explains the relevance of situational simulations in the construction engineering and management process. Most of the traditional simulations in construction belong to the optimization category. In contrast with the optimization simulations, situational simulations are not based on the interrelationships and trade-off among measurable variables. Situational simulations require the evaluation and interpretation of relevant information to "solve the crisis or problem" and are appropriate for problems or situations that offer the rapid unfolding of events and the pressure for decision-making. Situational simulations are also known as crisis management simulations, strategic simulations, and roleplaying simulations. The construction engineering and management process is represented through three different models: the process model, the product model, and the information model. The process model represents the construction process, the product model symbolizes the physical facility that is being built, and the information model characterizes the data generated about the product and the process. A description of each model is presented in this paper in order to illustrate the conceptual framework needed to establish the foundation for situational simulations.